Identifikasi Risiko Kerja dan Keluhan Gangguan Otot Rangka Pekerja Kios Berkah Jaya - Egi Asshidiq; Nur Rahman As'ad; Eri Achiraeniwati (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. Manual material handling (MMH) is an activity that is still widely carried out in Indonesia. MMH activities of moving and lifting objects can cause skeletal muscle injuries to work accidents if carried out exceeding ergonomic standards. Kiosk Berkah Jaya is a fertilizer kiosk whose job is to distribute fertilizer to 4 villages. MMH's work is still being carried out at the Berkah Jaya Kiosk. Every 1 week time limit workers are absent due to complaining of illness and needing treatment, and every 3-12 months there is frequent going in and out of workers. This condition was caused by the burden transferred to the process of distribution and procurement of Return Fertilizer which exceeded the standard limit. In the distribution process, the average weight of fertilizer that is transferred manually is 40 kg per sack with an average frequency of 30 times in 1 day. According to HSE, the weight of loads that can be moved manually by humans ranges from 1-15 kg and between 16-50 kg must be moved using tools [4]. The purpose of this study is to identify the risks carried out by workers at Kios Berkah Jaya and identify any complaints felt by workers. The method used to identify work complaints and risks uses SNI 9011: 2021. SNI 9011; 2021 which is divided into 3 stages, namely calling for a suitable method, distributing the GOTRAK questionnaire, level of work risk assessment with a list protecting potential hazards of ergonomic factors. The checklist of potential ergonomic hazard factors is divided into 2 parts, namely the checklist of potential hazard factors for ergonomic body posture and the checklist for potential hazard factors for manual lifting ergonomics. The results of the initial assistance showed that both workers (100%) complained of discomfort with a score of 12. The results of the GOTRAK questionnaire recapitulation of workers complained of discomfort in 11 body parts, namely the neck, shoulders, upper back, lower back, arms, hips, thighs, knees, calves and feet. The list of assessment results of checks for potential hazard factors for the ergonomics of fertilizer transfer work for distribution resulted in a score of 7 for body posture and 11 for manual lifting. Scores of body posture and removal of work fertilizers have a value of ≥7 which means the work is dangerous. Abstrak. Manual material handling (MMH) merupakan kegiatan yang masih anyak dilakukan Usaha Kecil Menengah (UMKM) di Indonesia. Kegiatan MMH memindahkan, dan mengangkat barang dapat menyebabkan cidera otot rangka hingga kecelakan kerja jika dilakukan melebihi batas standar ergonomi. Kios berkah jaya merupakan kios pupuk yang bertugas mendistribusikan pupuk ke 4 desa. Pekerjaan MMH sampai saat ini masih terjadi di Kios Berkah Jaya. Setiap kurun waktu 1 minggu pekerja absen dikarenakan mengeluhkan sakit dan harus berobat, dan setiap 3-12 bulan sering terjadi keluar masuk pekerja. Kondisi tersebut disebabkan oleh beban yang dipindahkan pada proses distribusi yang melebihi batas standar. Pada proses distribusi rata-rata berat pupuk yang dipindahkan secara manual adalah 40 kg per karung dengan rata-rata frekuensi 30 kali dalam 1 hari. Menurut HSE berat beban yang dapat dipindahkan secara manual oleh manusia berkisar antara 1 – 15 kg dan berat antara 16 – 50 kg harus dipindahkan menggunakan alat bantu [4]. Tujuan penelitian ini adalah mengidentifikasi risiko yang dilakukan oleh pekerja di Kios Berkah Jaya dan mengidentifikasi keluhan apa saja yang rasakan oleh pekerja. Metode yang digunakan untuk mengidentifikasi keluhan dan risiko kerja menggunakan SNI 9011 : 2021. SNI 9011: 2021 yang terbagi kedalam 3 tahap yaitu identifikasi untuk kecocokan metode, penyebaran kuesioner GOTRAK, penilaian level risiko kerja dengan daftar periksa potensi bahaya faktor ergonomi. Hasil identifikasi menunjukan kedua pekerja (100%) mengeluhkan ketidaknyamanan dengan skor 12. Hasil rekapitulasi kuesioner GOTRAK pekerja mengeluhkan ketidak nyamanan pada 11 bagian tubuh yaitu leher, bahu, punggung atas, punggung bawah, lengan, pinggul, paha, lutut, betis dan kaki. Hasil penilaian daftar periksa potensi bahaya faktor ergonomi pekerjaan pemindahan pupuk untuk distribusi didapat hasil skor 7 untuk postur tubuh dan 11 untuk pengangkatan beban manual. Skor postur tubuh dan pengangkatan pupuk pekerjaan mempunyai nilai ≥7 yang berarti pekerjaan tesebut berbahaya.